Penerapan Relaksasi Autogenik Terhadap Penurunan Kecemasan Pada Ibu Pre Kuretase Dengan Abortus Inkomplit - Pasambo, Yourisna; Ali, Dwi Rabiatul Adwiyah; Tamunu, Esther; Sarimin, Dorce Sisfiani; Pesak, Ellen; Tuegeh, Johana (POLTEKKES KEMENKES MANADO, 2023)
Background: Incomplete abortion is the partial loss of conception and the remaining tissue in the uterus. In this condition the mother is recommended to do curettage to remove and clean the existing tissue, prevent infection to overcome heavy bleeding. This can have a psychological impact on mothers who will undergo several series of actions, one of which is anxiety. Nurses play a role in reducing maternal anxiety so that mothers can go through each process well. The application of autogenic relaxation techniques can be a solution in increasing the relaxation response, providing a sensation of calmness towards a situation faced, to reduce maternal anxiety. The purpose of this study was to determine the application of autogenic relaxation in reducing the anxiety of mothers who will undergo curettage due to incomplete abortion. The research method is descriptive-qualitative with a case-study approach. For sample determination, we used a targeted sampling technique to determine the number of samples from up to four pregnant women who had undergone an incomplete abortion. Results: anxiety levels decreased after a 3-day self-relaxation intervention in four pregnant women with incomplete abortion before curettage . Conclusion: autogenic relaxation is effective in reducing anxiety levels in pre curettage pregnant women due to incomplete abortion.